(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: The emergence of Islamic banking (IB) in sub-Saharan Africa has been viewed as a catalyst for the economic growth and development of the sub-region. This study investigates the motivation, willingness to adopt, and determinants of IBs adoption in Liberia, a non-Islamic country in West Africa. Design/Methodology/Approach: Primary data were sourced from 210 Liberian citizens, accidentally sampled across four major counties, using semi-structured survey questionnaires. Descriptive statistics, simple percentages, statistical mean and the chi-square test of independence were used to analyse the data. Research Limitations: One of the main research limitations is that not all counties were included in determining the study sample size. Furthermore, specific components of the sample frame were not considered for selection because a convenience sampling approach was used. Findings: The results showed that the majority of the survey respondents (93.8%) were willing to acquire knowledge about the operation of the Islamic banking system. The decision to adopt the Islamic banking system was influenced by respondents’ socio-demographic characteristics, such as age, gender, educational attainment, employment status, and marital status. The findings provide critical insights into the incorporation of certain aspects of the Islamic banking system into Liberia’s banking sector. Practical Implications: Thus, stakeholders such as the Bank of Liberia should consider implementing pertinent governance structures and rules for IBs operations for risk minimisation, and resistance to economic crises in the country’s banking sector. Social Implications: The operationalisation of IBs will lead to job creation, economic growth and revenue mobilisation through corporate tax. Originality/Value: It contributes to the existing literature by highlighting the high interest of the respondents to adopt and practice the Islamic banking system in a non-Islamic country like the Republic of Liberia, defeating the general misconception about the non-adoption of Islamic bank principles, particularly the Sharia principle, by non-Islamic countries in the developing world.